2021
DOI: 10.3390/genes12050751
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study for Hypertensive Kidney Disease in Korean Men

Abstract: Hypertension is one of the major risk factors for chronic kidney disease (CKD), and the coexistence of hypertension and CKD increases morbidity and mortality. Although many genetic factors have been identified separately for hypertension and kidney disease, studies specifically focused on hypertensive kidney disease (HKD) have been rare. Therefore, this study aimed to identify loci or genes associated with HKD. A genome-wide association study (GWAS) was conducted using two Korean cohorts, the Health Examinee (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…conducted a large GWAS study of over 20 000 Korean men, and identified FANCM as the genetic gene associated with HKD. This research found that FANCM variation predominantly occurred in the glomerulus, tibial artery and aorta, and was strongly correlated with eGFR and creatinine ratio 45 …”
Section: The Theory Of the Kidney As The Foundation Of Heritability W...mentioning
confidence: 65%
See 1 more Smart Citation
“…conducted a large GWAS study of over 20 000 Korean men, and identified FANCM as the genetic gene associated with HKD. This research found that FANCM variation predominantly occurred in the glomerulus, tibial artery and aorta, and was strongly correlated with eGFR and creatinine ratio 45 …”
Section: The Theory Of the Kidney As The Foundation Of Heritability W...mentioning
confidence: 65%
“…This research found that FANCM variation predominantly occurred in the glomerulus, tibial artery and aorta, and was strongly correlated with eGFR and creatinine ratio. 45 Despite the considerable strides made in genetic research on kidney function, there remains numerous difficulties in translating these findings into clinical practice for preventing or treating CKD and frailty. It is important to acknowledge that genetic diversity can vary based on race and ethnicity, which can impact the efficacy of drugs across different groups.…”
Section: Yearmentioning
confidence: 99%
“…Their coexistence has serious implications for human health increasing morbidity and mortality, especially from cardiovascular disease [22]. Several factors contribute to the concurrent presence of hypertension and kidney disease [23], including the contribution of a genetic component, as suggested by recent studies highlighting genes involved in both hypertension and kidney disease [24,25]. In the present study, to increase the understanding of the genetic connection in between, we evaluated the genetic variability of the heteromeric amino acid transporter LAT2/4F2hc (SLC7A8/SLC3A2 genes) in subjects strati ed according to presence/absence of CKD, evaluated by estimated glomerular ltration rate (eGFR), and presence/absence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Their coexistence has serious implications for human health increasing morbidity and mortality, especially from cardiovascular disease [ 23 ]. Several factors contribute to the concurrent presence of hypertension and kidney disease [ 24 ], including the contribution of a genetic component, as suggested by recent studies highlighting genes involved in both hypertension and kidney disease [ 25 , 26 ]. In the present study, to increase the understanding of the genetic connection in between, we investigated the genetic variability of the SLC7A8/SLC3A2 genes, coding for the heteromeric transporter LAT2/4F2hc which mediates the cell-uptake of L-DOPA in kidney, in subjects stratified according to presence/absence of CKD and presence/absence of hypertension.…”
Section: Discussionmentioning
confidence: 99%